The influence of the “hot”-dimer adsorption mechanism on the kinetics of a monomer-dimer surface reaction - Pereyra, V. D. (1993)
“Hot” dimers are molecules which after adsorption dissociate and each of the remaining “hot” monomers fly apart up to a maximum distance R from the original adsorption site. The influence of the “hot”-dimer adsorption mechanism on relevant aspects of the bimolecular catalyzed reaction of the type A − (1/2)B2(“hot”) → AB is studied by means of the Monte-Carlo simulation technique. The temporal evolution of both the reactant's coverages as well as the rate of AB-production is evaluated and discussed. Due to the enhanced probability of “hot” species for encounters with other adsorbed particles, the rate of AB-production becomes faster when increasing R. This behavior may be relevant in the dynamic of some catalyzed reactions such as for example the oxidation of carbon monoxide on transition metal surfaces, i.e. A≡CO, B2≡O2, and AB≡CO2. Also the sticking coefficient of “hot” dimers and the average distance traveled by the “hot” monomers are evaluated and discussed.